Applying Various Types of Loading on Continuous Deep Beams Using Strut and Tie Modelling - Saleem Abdul-Razzaq, Khattab; Mustafa Jalil, Ali; H. Mohammed, Abbas (International Journal of Engineering and Technology, 2018)
This work aims at presenting detailed procedures companied by numerical examples for designing reinforced concrete two span continuous deep beams under various types of loading; one concentrated force, two concentrated forces and uniform load for each span. Analysis and design was conducted based on Strut and Tie modeling (STM) of ACI 318M-14 since they contain significant extents of D-regions and they show a marked truss or tied arch action. It was found that changing the loading type has a significant impact on the capacity for the same specimen that has the same dimensions, concrete and steel properties, in addition to the same amount and arrangement of steel reinforcement. In more detail, the increase in the number of concentrated forces causes an obvious increase in ultimate capacity due to the reduction in span to overall height (a/h) ratio and the increase in the value of the strut-tie angle, which causes shortening in the length of the strut. Therefore, the ultimate capacity increased by about (44-70) % when the applied load was changed from 1-concentrated force to 2-concentrated forces or to uniformly distributed load. Â